Desain Hipotesis Lintasan Belajar Volume Bangun Ruang Sisi Datar Pada Sekolah Menengah Pertama: Berbasis Teori Van Hiele - Ernawati Jais; Anwar Anwar; Raizal Rezky (Postgraduate, University of Mataram, 2023)
This study aimed to develop a hypothesis learning trajectory that can help students understand the concept of volume polyhedron based on van Hiele's theory. This study used a design research method with a type of validation studies to create a design framework for learning trajectories passed by students in mathematics learning. The study focusedon the first stage, i.e. preliminary design to develop a sequence of volume learning activities to polyhedron used the stages of the van hiele theory. The results of this study show the learning activities that will be traversed by students and teachers in understanding the concept of volume up the flat side space through the four stages of van Hiele i.e. 1) visualization stage atÂ which students find the prism volume; 2) analysis phase at which students find the volume of cuboid obtained from the prism volume; 3) informal deduction phase at which student finds the volume of the cube from the building of the cuboid with the same length and height; 4) formal deduction phase at which student to find the formula for the volume of pyramid.